2011
DOI: 10.1063/1.3627231
|View full text |Cite|
|
Sign up to set email alerts
|

Van der Waals supercritical fluid: Exact formulas for special lines

Abstract: In the framework of the van-der-Waals model, analytical expressions for the locus of extrema (ridges) for heat capacity, thermal expansion coefficient, compressibility, density fluctuation, and sound velocity in the supercritical region have been obtained. It was found that the ridges for different thermodynamic values virtually merge into single Widom line only at T < 1.07Tc, P < 1.25Pc and become smeared at T < 2Tc, P < 5Pc, where Tc and Pc are the critical temperature and pressure. The behavior of the Batsc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 18 publications
2
40
0
8
Order By: Relevance
“…The WL of supercritical noble gases, Lennard-Jones and van der Waals fluids was recently studied by experiments and simulations [23][24][25][26][27] . In particular, a recent experimental work has paved the way to a more profound knowledge of hot dense fluids by detecting a crossover in sound velocity of supercritical fluids of noble gases connected to the WL 26 .…”
mentioning
confidence: 99%
“…The WL of supercritical noble gases, Lennard-Jones and van der Waals fluids was recently studied by experiments and simulations [23][24][25][26][27] . In particular, a recent experimental work has paved the way to a more profound knowledge of hot dense fluids by detecting a crossover in sound velocity of supercritical fluids of noble gases connected to the WL 26 .…”
mentioning
confidence: 99%
“…Finally, we would like to draw attention to the fact that various relations that follow from the WE not only for the ideal lines also appear to be valid, at least qualitatively, for more complex systems. For example, in the supercritical fluid region, the WE "generates" a number of lines that significantly enrich the understanding of this region [23,24]. Among these lines, the line that determines the inversion temperature in the Joule-Thomson process appears to be useful to us.…”
Section: Thermophysical Properties Of Materialsmentioning
confidence: 96%
“…Almost 100 years ago, J. Timmermans proposed an empirical relation for the compressibility factor at the critical point that correlates it with the Boyle density (see [4,22]) as (23) The experimental results enabled refinement of the relation [29] by introducing a small correction exponent Z с = (n с /n B ) 1 + α where α = 0.019. Taking into consideration Eq.…”
Section: + β + =mentioning
confidence: 99%
See 1 more Smart Citation
“…For some years a so called Widom line, which is a line of supercritical maxima of correlation length and thermodynamic response functions (isobaric heat capacity c P , isothermal compressibility k T , heat expansion coefficion α P ) in fluids, was used to extend a liquid-gas coexistence line into supercritical region1. Later on it was shown that Widom line rapidly splits into a bunch of lines of maxima of different quantities as soon as one goes several dozens percent away from the critical point23. Nevertheless the concept of Widom line is quite important for the description of the anomalous behavior near critical point.…”
mentioning
confidence: 99%